SYARI’AH DALAM PERSPEKTIF PELAKU BISNIS MLM SYARI’AH AHADNET INTERNASIONAL ( Studi Kasus di Kota Semarang ) - Choirul Huda (Economica: Jurnal Ekonomi Islam, 2013)
PT. Ahadnet International, a business Multi Level Marketing (MLM) Syariah, is a MLM business operations based on the principles of syari'ah . The business attracted many people from among Muslims because it offers businesses with marketing Islamic halal products and toyyib. No doubt, many Muslims were later merged into the Ahadnet MITRANIAGA. Nevertheless, the Muslims interests of this business does not mean not raising the issue. Labeling the word “Syariah” is attached to the naming MLM International Syari’ah Ahadnet it needs proper interpretation. Wrong interpretation of the word shariah for the Ahadnet International MLM syari’ah business will bring counterproductive, both for the company, MITRANIAGA and for Islam itself. Seeing this phenomenon, it is through this study, researchers are trying to see how far the understanding of the actors (MITRANIAGA) International Ahadnet the term shari’ah. Their understanding of Shari’ah will affect the way they work on the syariah business in genera,  particularly MLM syari’ah business